Enzymatically releasable polyethylene glycol – host defense peptide conjugates with improved activity and biocompatibility - Drayton, Matthew; Alford, Morgan A.; Pletzer, Daniel; Haney, Evan F.; Machado, Yoan; Luo, Haiming D.; Overall, Christopher M.; Kizhakkedathu, Jayachandran N.; Hancock, Robert E.W.; Straus, Suzana K. (Journal of controlled release, 2021)
Host defense peptides (HDPs) have been the subject of great interest for the treatment of multidrug-resistant bacterial infections due to their multimodal activity and low induction of resistance. However, aggregation, toxicity, and short biological half-life have limited their applicability for clinical treatment. Many methods have been explored to alleviate these issues, such as polymer (e.g., polyethylene glycol (PEG)) conjugation, but these are often accompanied by reductions in the activity of the HDP. Here, we detail the design of a novel PEG-HDP conjugate incorporating an enzymatic cleavage sequence targeting matrix metalloproteinases (MMPs) that accumulate at sites of inflammation and infection. Addition of the cleavage sequence onto either the N- or the C-terminal region of the parent peptide (peptide 73, a derivative of the HDP aurein 2.2) was explored to determine the location for optimal antimicrobial activity following MMP cleavage; furthermore, the susceptibility of the peptide to MMP cleavage after conjugation to 2 kDa or 5 kDa PEG was examined. The top candidate, L73, utilized an N-terminal cleavage site that was subsequently conjugated to a 2 kDa PEG polymer. Both L73 and the conjugate exhibited no antimicrobial activity in vitro until cleaved by purified MMP, which liberated a peptide fragment with 16- or 63-fold improved activity, respectively, corresponding to a minimum inhibitory concentration (MIC) of 8 μg/mL, comparable to that of peptide 73 (4 μg/mL). Furthermore, PEG conjugation improved the blood compatibility and reduced the aggregation tendency of the HDP in vitro, indicating enhanced biocompatibility. When administered as a single subcutaneous dose (~3.6 mg, or a peptide concentration of 142 mg/kg) in a mouse abscess model of high-density methicillin-resistant Staphylococcus aureus (MRSA) infection, the conjugate displayed strong activity, reducing abscess size and bacterial load by 73.3% and 58-fold, respectively. This activity was completely lost when the cleavage site was rendered resistant to MMPs by the substitution of two d-amino acids, supporting the hypothesis that antimicrobial activity was dependent on cleavage by MMPs, which were shown here to increasingly accumulate at the abscess site up to 18 h post infection. Finally, the conjugate displayed biocompatibility in vivo, with no identifiable toxicity or aggregation. [Display omitted]